Potential Pain in Fish and Decapods: Similar Experimental Approaches and Similar Results - Elwood, Robert W. (Frontiers in Veterinary Science, 2021)
I review studies that examined the possibility of pain experience in fish and note how they provided guidance on general methods that could be applied to other animals such as decapod crustaceans. The fish studies initially reported the occurrence of prolonged rocking movements in trout and rubbing of their lips if they were injected with acetic acid. Subsequent studies examined the role of morphine in reducing these activities and examined shifts in attention when responding to noxious stimuli. Various studies take up these themes in decapods. The results reported for the two taxonomic groups are remarkably similar and indicate that responses of both go beyond those expected of mere nociceptive reflex. Thus, the idea of pain cannot be dismissed by the argument that fish and decapods respond only by reflex. The responses of both clearly involve central processing and pain experience, although not proven for either, is a distinct possibility. These studies have been the subjects of highly critical opinion pieces and these are examined and rebutted. The conclusion is that both fish and decapods should be awarded consideration for their welfare.